Prolonged length of stays and its associated factors among pediatric surgical patients in Oromia, Central part of Ethiopia: A cross-sectional study - Redwan Nesha; Haymanot Mezmur; Yohannes Baye; Fentahun Meseret; Mulualem Keneni; Ayichew Alemu; Yalew Mossie; Henok Legesse (PLoS ONE, 2025)
Background Pediatric surgical diseases are conditions that require surgery in children to save lives, prevent disability, or provide palliative care. Surgeries can be major or minor based on factors like severity, and complexity. Prolonged hospital stay could significantly affect the limited resources of the hospital, and further lead to post-operative complications, and poor surgical outcome. Identifying the factors that contribute to longer hospital stays could improve quality of patient care and service delivery. However, there is limited evidence in Ethiopia, particularly among paediatrics population. Hence, this study aimed to assess the length of hospital stay and its associated factors among pediatric surgical patients admitted to Adama Comprehensive Specialized Hospital and Asella Teaching Hospital, Oromia, Ethiopia. Methods Institutional based cross-sectional study was conducted through secondary data extraction from February 1, 2023, to January 30, 2024. A simple random sampling technique was employed to select 422 pediatric patients admitted to the surgical units. SPSS version 26 was utilized for analysis and data was presented in frequency, percentage, tables and figures. The association between independent variables and dependent variable (Prolonged Length of Hospital Stay) was assessed using binary logistic regression. A length of hospital stays for more than or equal to 75th percentile (≥ 12.5 days) was considered as prolonged. Finally, variables with p-value <0.05 were considered statistically significant. Results The prevalence of prolonged length of stay was found to be 19.6% [95% CI: 15.8%, 23.4%]. Undernutrition [AOR: 2.6; 95% CI: 1.11,6.08], children admitted due to trauma [AOR: 4.1; 95% CI: 1.75, 9.83], and postoperative complications [AOR: 7.8; 95% CI: 3.99, 15.6] were positively associated with the outcome variable. Whereas, emergency admission [AOR: 0.30; 95% CI: 0.14, 0.61], was negatively associated with prolonged length of stay. Conclusion Approximately one-fifth of the participants experienced prolonged in hospital stays. Therefore, clinical practitionars, hospital administrators and respective stackholders could significantly reduce the childrens length of stay and utilize hospital resources effectively through screening nutritional status, keen attention to trauma admission and monitoring and managing post-operative complications as early as possible.Moreover,ensuring all children to have food security may result in shorter stay in the hospital. Expansion of surgical work force could also improve patient outcome following surgery among paediatrics population.